Influence of Return on Equity (ROE), The Price Earnings Ratio (PER) and the Capital Structure of The Company's Share Price Against the Sub Sectors of Transport Registered in Bursaefek Indonesia (BEI) the Period of 2015-2018 - Novien Rialdy (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2019)
This research aims to find out whether the influence of Return on Equity (ROE), the Price Earnings Ratio (PER) and the Capital structure of the company's share price against the Sub Sectors of transport registered in Indonesia stock exchange (BEI) of the period of 2015-2018 well partially as well as simultaneous. The research method used is the quantitative approach, this type of research is descriptive and explanatory nature. This study contains a population of 39 companies with samples as many as 9 companies for the 4-year research period by using Purposive sampling technique as the determination of the sample. Engineering data collection, documentation, data types used are secondary data in financial statements BEI. The analysis of the data used is multiple linear regression. Prior to testing the hypothesis will be tested using the test data assuming the classics. The results of the analysis of the coefficient of determination in getting adjusted R square values of 0.382 mean variation variable the company stock price can be explained by variation in return on equity, variable price earnings ratio and structure of capital was amounted to 38.2% While the rest of 61.8% is explained by other free variables. The results showed that the simultaneous return on equity, price earnings ratio and capital structure influenced positively and significantly to the stock price with value and the value of 2.90 > 6.591 significant 0.01< 0.05. Partially, variable return on equity in partial positive and significant effect against the price of a stock with a value of 2.03693 > 3.739 and significant value of 0.01 < 0.05, The Price earnings ratio of positive and significant effect against the price of a stock with a value of 2.315 > 2.03693 and significant value of 0.027 < 0. 05.. partially capital structure variables do not affect the positive and significant price shares with a value of 0.448 < 2.03693 and significant value of 0.657 > 0.05.